Conchology Variations in Species Identification of Pachychilidae (Mollusca, Gastropoda, Cerithiodea) through Multivariate Analysis - Hadi Hamli; Norsyafiqah Abdul Hamed; Sharifah Hazirah Syed Azmai; Mohd Hanafi Idris (Tropical Life Sciences Research, 2020)
Pachychilidae is one of the freshwater gastropod family which was previously known under the Potamididae and Thiaridae families. Studies on freshwater gastropods especially on conchcology examinantions are still inadequate compared to marine gastropods. Morphological and morphometric studies of gastropods are practically used to identify and differentiate between species and necessary to complement molecular studies due to its low cost and tolerable resolving power of discrimination. The aim of the current study is to provide information on morphological and morphometric characteristics of Pachychilidae in Bintulu, Sarawak stream. A total of 20 individuals from each species of Sulcospira testudinaria, Sulcospira schmidti, Brotia siamensis, and Tylomelania sp. from Pachychilidae familiy were collected at three different sites from a small stream within the Bintulu area. Fourteen measurement of shell morphometrics were converted into proportioned ratios and analysed for univariate and multivariate analysis. Three shell morphometric (Aperture width, AW; Whorl width, WW2; and, Interior anterior length, AINL) of Pachychilidae indicated significant differences (P < 0.05) between species. However, multivariate analysis revealed that these shell morphometrics are pre-eminent factors to discriminate genus Sulcospira, Brotia and Tylomelania, as well as between Sulcospira species. This current study also suggests that these three characteristics are unique to Sulcospira species due to strong distinction among species. Findings on these three characteristics are significant for Sulcospira spp. as this study is the first shell morphometric report on the Pachychilidae species in Sarawak. Pachychilidae adalah salah satu keluarga gastropod air tawar yang dahulu dikenali sebagai keluarga Potamididae dan Thiaridae. Kajian mengenai gastropod air tawar masih tidak mencukupi berbanding gastropod laut. Kajian morfologi dan morfometrik mengenai gastropod digunakan secara praktikal untuk mengenal pasti dan membezakan antara spesies dan diperlukan sebagai pelengkap untuk kajian molekul kerana kos yang rendah dan kebolehan pembezaan. Tujuan kajian ini adalah untuk menyediakan lebih banyak maklumat mengenai ciri-ciri morfologi dan morfometrik Pachychilidae di Sarawak. Sejumlah dua puluh sampel individu dari Sulcospira testudinaria, S. schmidti, Brotia siamensis, dan Tylomelania sp. daripada keluarga Pachychilidae dikumpulkan dari tiga kawasan sungai kecil yang berlainan dalam kawasan Bintulu. Empat belas ciri-ciri cengkerang yang diukur telah diubah menjadi nisbah yang dianggarkan dan dianalisis untuk analisa univariat dan multivariat. Tiga ciri cengkerang (AW, WW2, AINL) Pachychilidae menunjukkan perbezaan ketara (P < 0.05) antara spesies. Walau bagaimanapun, analisis multivariate mendedahkan bahawa ciri-ciri cengkerang ini merupakan faktor utama untuk membezakan spesies Sulcospira dari Brotia dan Tylomelania, serta antara spesies Sulcospira. Kajian ini menunjukkan bahawa ketiga-tiga ciri ini adalah unik kepada spesies Sulcospira kerana perbezaan yang kuat antara spesies. Penemuan terhadap ciri-ciri tertentu ini penting bagi Sulcospira spp. kerana kajian ini adalah laporan pertama mengenai morfometrik cengkerang spesies Pachychilidae di Sarawak.